Geothermal Heat Flux Reveals the Iceland Hotspot Track Underneath Greenland. Issue 16 (24th August 2018) - Martos, Yasmina M.; Jordan, Tom A.; Catalán, Manuel; Jordan, Thomas M.; Bamber, Jonathan L.; Vaughan, David G.
Abstract: Curie depths beneath Greenland are revealed by spectral analysis of data from the World Digital Magnetic Anomaly Map 2. A thermal model of the lithosphere then provides a corresponding geothermal heat flux map. This new map exhibits significantly higher frequency but lower amplitude variation than earlier heat flux maps and provides an important boundary condition for numerical ice‐sheet models and interpretation of borehole temperature profiles. In addition, it reveals new geologically significant features. Notably, we identify a prominent quasi‐linear elevated geothermal heat flux anomaly running northwest–southeast across Greenland. We interpret this feature to be the relic of the passage of the Iceland hotspot from 80 to 50 Ma. The expected partial melting of the lithosphere and magmatic underplating or intrusion into the lower crust is compatible with models of observed satellite gravity data and recent seismic observations. Our geological interpretation has potentially significant implications for the geodynamic evolution of Greenland. Plain Language Summary: Heat escaping from the Earth's interior provides important clues about areas of geology and geodynamics. In addition, where a region is covered by an ice sheet, such as Greenland, variations in the heat supplied from the Earth's interior can potentially influence how the ice flows, and hence its future changes. Unfortunately, in ice covered regions direct measurements of heat flow are limited to sparse boreholes, meaning this important quantity is poorly understood. In this study we used variations in the Earth's magnetic field to map out the variations in the amount of heat being supplied to the base of the Greenland Ice Sheet from the Earth's interior. Ice sheet models incorporating these new and improved results will help better constrain future predictions of ice sheet evolution. Overall, the new map not only shows less extreme variations than previous studies, but also reveals a previously unseen band of warmer than expected rock stretching northwest to southeast across Greenland. This band, together with lithospheric models derived from gravity data, is interpreted to be the scar left as the Greenland tectonic plate moved over a region of hot upwelling mantle (the material beneath the tectonic plates), which now underlies Iceland. Key Points: A Greenland‐wide heat flux map is derived from magnetic data identifying a signature related to the Iceland hotspot track Bouguer anomalies are consistent with thicker crust and underplating by the plume The heat flux map provides a new constraint for thermomechanical models of the Greenland Ice Sheet